Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ajpath.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Colorectal Cancer Phenomics from Fundamental and Organotypic Model Studies

Abstract: Colorectal cancer (CRC) diagnosis and prognostic stratification are based on histopathologic assessment of cell or nuclear pleomorphism, aberrant mitotic figures, altered glandular architecture, and other phenomic abnormalities. This complexity is driven by oncogenic perturbation of tightly coordinated spatiotemporal signaling to disrupt multiple scales of tissue organization. This review clarifies molecular and cellular mechanisms underlying common CRC histologic features and helps understand how the CRC geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 99 publications
(221 reference statements)
0
10
0
Order By: Relevance
“…In addition, RNA interference of RhoA or treatment with a ROCK inhibitor eliminated the inverted polarity [21,23,24]. The similarity between inverted features of polarity and the MPC phenotype has been suggested [26]. On the other hand, the model MPC system used in this study is different from MDCK cells in some ways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNA interference of RhoA or treatment with a ROCK inhibitor eliminated the inverted polarity [21,23,24]. The similarity between inverted features of polarity and the MPC phenotype has been suggested [26]. On the other hand, the model MPC system used in this study is different from MDCK cells in some ways.…”
Section: Discussionmentioning
confidence: 99%
“…To survive in such conditions, cells must respond either by inhibiting pro‐apoptotic signaling or by activating anti‐apoptotic mechanisms (5,6). It is likely that, in addition to anoikis resistance, other aberrations, such as suppression of apical polarity signaling (23), contribute to formation of the putative AR structures. Supporting the concept of multicellular groups without ECM contact indicating anoikis resistance, we have recently shown that transfection of Caco‐2 cells with mutated KRAS or BRAF gene induces anoikis resistance (12) and, simultaneously, changes 3D growth from simple unilayered cysts to either focal piling of the cells reminiscent of MIP structures or solid growth reminiscent of solid structures, respectively (12).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, CRC diagnosis and prognostic stratification are based on histopathologic assessment of cell or nuclear pleomorphism, aberrant mitotic figures, altered glandular architecture, and other phenomic abnormalities [94]. From this standpoint, complexity may involve oncogenic perturbation of spatiotemporal signaling, leading to disruption at multiple levels of tissue organization.…”
Section: Consensus Molecular Subtypes (Cms Classification)mentioning
confidence: 99%